Problems with the "Problems" with Psychophysical Causation - McKay, Noah (Stance: an international undergraduate philosophy journal, 2019)
In this essay, I defend a mind-body dualism, according to which human minds are immaterial substances that exercise non-redundant causal powers over bodies, against the notorious problem of psychophysical causation. I explicate and reply to three formulations of the problem: (i) the claim that, on dualism, psychophysical causation is inconsistent with physical causal closure, (ii) the claim that psychophysical causation on the dualist view is intolerably mysterious, and (iii) Jaegwon Kim’s claim that dualism fails to account for causal pairings. Ultimately, I conclude that these objections fail and that dualist interactionism is no more problematic or mysterious than physical causation.